Effects of Waste Organic Samples and Extraction Methods towards the Absorption Range of Carbon Nanodots and How it Affects Plants’ Growth - Tanujaya, Joshua (International Journal of Regional Innovation, 2024)
Carbon-nanodots (CND) were nanotechnologies possessing low toxicity, photoluminescence, and biocompatibility qualities which were applicable to various aspects namely in assisting plant growth. Chloroplasts were essential in plant growth that is to absorb sunlight, however the UV spectrum’s wavelength range which could be absorbed was limited and therefore the photosynthesis efficiency was also inadequate. Nevertheless, chloroplasts which integrated with CND would have wider range of the UV absorptivity that was the combination from the absorptivity of chloroplast and CND. Therefore, the CND needed would require a broad absorptivity range. CNDs were extractable from various waste organic samples with a plethora of extraction methods. This study reviews the organic samples and the methods which were able to produce CND with widest absorptivity range and the effects CND gave to plant growth. The data used were the outcome of evaluating literatures. It was discovered that CND synthesized from dragon fruit skin and pear fruit skin have the widest absorptivity which was 70 nm which could be affected by numerous amounts of chromophore group in the sample and the most effective extraction methods were those which utilized micro waves as it has disadvantage being only that it couldn’t work on large number of samples and advantages being a fast process of extraction and small energy required. CND contributed positive effects to plants by increasing sprout length, root length, fresh root weight, dry root weight, fresh sprout weight, dry sprout weight, fresh plant weight, dry plant weight, root strength, stem length, Rubisco activity, and chlorophyll content.